Legal Case Linking Divorce Proceedings to Development of Schizophrenia: Court's Ruling Number 675/Pd.G/2021.Pa.Pn - Abdul Hafizh; Hertasmaldi; Faisal Efendi (Pusat Penelitian dan Pengabdian pada Masyarakat (P3M) Sekolah Tinggi Agama Islam As-Sunnah, 2023)
This article discusses a wife who filed a lawsuit with the Painan religious court. Even though in the Koran it has been explained that it is men who have the right to divorce, but because in this household there has been disharmony and violence because the husband has schizophrenia. The researcher used a liberar sech type of research (literature review). The research information that became primary data was the decisions of judges at the Painan Religious Court, while secondary data came from books, journals and references from laws. The guidelines for writing this research used the book Lukman Hakim, et al, guidelines for writing scientific papers at the Islamic College of Religion, 2017. The results of the study can be concluded that, the background of the wife who submitted a lawsuit to the Painan religious court was because her husband had committed violence and there had been quarrels that continously.